Race, Religion, and the Politics of Violence: Analysis of Terrorism Labeling in the Cases of Omar Mateen and Robert Bowers in American Mass Shootings - Aisyah Safitri; Annisa Nur Aglima Pradani; Nabila Ananda husainu (PT. Data Jaringan Visual Indonesia (Djava), 2026)
This article explores how factors such as race, religion, and political power influence the classification of violent acts as “terrorism,” focusing on two mass shootings in the United States: the 2016 Pulse Nightclub attack by Omar Mateen and the 2018 Tree of Life Synagogue attack by Robert Bowers. Using a qualitative comparative case study, the research reveals how the application of the terrorism label often depends on the perpetrator’s identity. Despite both attackers having clear ideological motives, Mateen a Muslim of colorwas swiftly labeled a terrorist, while Bowers a white man driven by white supremacist beliefs was more often described in terms of hate crime or mental health issues. The study highlights that the term “terrorism” functions less as an objective legal definition and more as a social and political construct shaped by racial and religious biases. By analyzing narratives, media portrayals, and policy responses, the article shows that these labeling practices significantly impact security strategies, shape public opinion, and contribute to the marginalization of minority groups. Ultimately, the article argues for a more neutral and consistent approach to defining and addressing ideological violence, emphasizing the need to critically examine how power dynamics shape discourse around domestic extremism.